PROLACTIN AND REPRODUCTION - Ascenzo Cabello, Jorge (2015)
Prolactin (PRL) is the oldest hormone secreted by the pituitary gland. This, or a similar, has been present in vertebrates, from fish to mammals, from 400 million years ago, speaking primarily in their growth, development, metabolism, osmoregulation (controlling water and electrolyte balance) and intervening in their reproduction, as well as the constitution of the ectoderm and act synergistically or antagonistically with steroid hormones.